DNA metabarcoding reveals the significant influence of anthropogenic effects on microeukaryotic communities in urban waterbodies. (15th September 2021) - Abdullah Al, Mamun; Xue, Yuanyuan; Xiao, Peng; Chen, Huihuang; Zhang, Chaoshuo; Duan, Ming; Yang, Jun
Abstract: Biological monitoring and assessment are the first and most fundamental steps towards diagnosing ecological or environmental quality. Increasing anthropogenic impact on urban ecosystems has prompted the development of less expensive and more efficient bioassessment approaches. Generally, a morphospecies based approach is effective for plants and large organisms but challenging for the microbial biosphere. To overcome this challenge, we used high-throughput DNA sequencing for predicting anthropogenic effects on microeukaryotic communities in urban waterbodies along a pollution gradient in Wuhan City, central China in summer 2019. Our results indicated that microeukaryotic community structure was distinct between non-urban polluted reservoir and urban polluted waterbodies. The heterogeneity of environmental condition significantly affected the microeukaryotic diversity, community structure, and species interactions. Integrated co-occurring network analysis revealed that the pollution gradient has a significant adverse impact on network complexity and network dissimilarity. These results revealed that the significant variation in anthropogenically-driven environmental condition shaped microeukaryotic communities in urban freshwater ecosystems. Furthermore, we observed that the relative abundance of indicative OTUs were significantly and negatively correlated with pollution level and these indicative OTUs could be used to predict the water quality status with up to 77% success. Thus, our multiple approaches combining 18S rDNA amplicon sequencing, co-occurring network and indicator species analyses suggest that this study gives a novel approach based on microeukaryotic communities to assess and predict the water quality status of urban aquatic environments. Graphical abstract: Image 1 Highlights: Environmental heterogeneity drove variation in microeukaryotic community composition. Anthropogenic pollution showed negative influence on microeukaryotic interactions. Co-occurring network revealed a greater dissimilarity along pollution gradient. Microeukaryotic indicators may improve the precision monitoring of water quality.